Connect with experts and get insightful answers to your questions on IDNLearn.com. Our platform is designed to provide quick and accurate answers to any questions you may have.
Sagot :
To find the value of [tex]\( p \)[/tex] that makes the equation [tex]\( -3p + \frac{1}{8} = -\frac{1}{4} \)[/tex] true, follow these step-by-step instructions:
1. Start with the given equation:
[tex]\[ -3p + \frac{1}{8} = -\frac{1}{4} \][/tex]
2. First, isolate the term with [tex]\( p \)[/tex]. Subtract [tex]\(\frac{1}{8}\)[/tex] from both sides of the equation:
[tex]\[ -3p = -\frac{1}{4} - \frac{1}{8} \][/tex]
3. To subtract the fractions, find a common denominator. The least common denominator of 4 and 8 is 8. Rewrite [tex]\(-\frac{1}{4}\)[/tex] as an equivalent fraction with the denominator 8:
[tex]\[ -\frac{1}{4} = -\frac{2}{8} \][/tex]
4. Now the equation becomes:
[tex]\[ -3p = -\frac{2}{8} - \frac{1}{8} \][/tex]
5. Combine the fractions on the right side:
[tex]\[ -3p = -\frac{3}{8} \][/tex]
6. Next, solve for [tex]\( p \)[/tex] by dividing both sides of the equation by -3:
[tex]\[ p = \frac{-\frac{3}{8}}{-3} \][/tex]
7. Simplify the right side:
[tex]\[ p = \frac{3}{8} \times \frac{1}{3} = \frac{3}{24} = \frac{1}{8} \][/tex]
Therefore, the value of [tex]\( p \)[/tex] that makes the equation true is:
[tex]\[ p = \frac{1}{8} \][/tex]
1. Start with the given equation:
[tex]\[ -3p + \frac{1}{8} = -\frac{1}{4} \][/tex]
2. First, isolate the term with [tex]\( p \)[/tex]. Subtract [tex]\(\frac{1}{8}\)[/tex] from both sides of the equation:
[tex]\[ -3p = -\frac{1}{4} - \frac{1}{8} \][/tex]
3. To subtract the fractions, find a common denominator. The least common denominator of 4 and 8 is 8. Rewrite [tex]\(-\frac{1}{4}\)[/tex] as an equivalent fraction with the denominator 8:
[tex]\[ -\frac{1}{4} = -\frac{2}{8} \][/tex]
4. Now the equation becomes:
[tex]\[ -3p = -\frac{2}{8} - \frac{1}{8} \][/tex]
5. Combine the fractions on the right side:
[tex]\[ -3p = -\frac{3}{8} \][/tex]
6. Next, solve for [tex]\( p \)[/tex] by dividing both sides of the equation by -3:
[tex]\[ p = \frac{-\frac{3}{8}}{-3} \][/tex]
7. Simplify the right side:
[tex]\[ p = \frac{3}{8} \times \frac{1}{3} = \frac{3}{24} = \frac{1}{8} \][/tex]
Therefore, the value of [tex]\( p \)[/tex] that makes the equation true is:
[tex]\[ p = \frac{1}{8} \][/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Find reliable answers at IDNLearn.com. Thanks for stopping by, and come back for more trustworthy solutions.